The Effectiveness of Cooperative Learning Using the Contextual Teaching and Learning (CTL) Approach Based on Thematic Quranic Verses on Learning Outcomes and Spiritual Attitudes - Sulistiyawati; Wa Ode Harlis; Cecilia Yanuarief; Qatrunnada Ummu Kultsum (CV. Publikasi Indonesia, 2026)
The integration of scientific concepts with religious values is an important aspect of developing holistic education, particularly in biology learning that aims not only to improve cognitive achievement but also to strengthen students’ spiritual attitudes. However, biology learning, especially on psychotropic materials, often remains focused on conceptual understanding and has limited connections with students’ real-life experiences and moral awareness. This study aimed to examine the effectiveness of cooperative learning using the Contextual Teaching and Learning (CTL) approach based on thematic Quranic verses on students’ learning outcomes and spiritual attitudes in psychotropic material. This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The research sample consisted of 27 students of class XI science at MAN 4 Bantul, divided into an experimental group and a control group. Data were collected through learning outcome tests and spiritual attitude questionnaires, while data analysis was conducted using validity, reliability, N-gain, paired sample t-test, and independent sample t-test. The results showed that the experimental class experienced greater improvement in learning outcomes with an N-gain score of 0.43 (medium category) compared with the control class with an N-gain score of 0.25 (low category). Statistical analysis revealed significant differences between groups, while the experimental class also demonstrated higher spiritual attitude scores. In conclusion, cooperative learning integrated with CTL and thematic Quranic verses effectively enhances students’ biological understanding and contributes to strengthening spiritual values in learning.